PENERAPAN MODEL CREATIVE PROBLEM SOLVING PADA MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS X SMAN 1 TAMBUSAI UTARA - Erna Habibah; Muhammad Nor; M. Rahmad ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research aimed to describe and find out the improvement of students interest learning by applying creative problem solving (CPS) model. The research used quasi experimental model, with nonequivalent control group design. The subject are 70 students of class X SMAN 1 Tambusai Utara, divide into experiment class and control class. Data of the research is score of interest before and after applying creative problem solving model with descriptive and inferential analysis. Analysis of the increase of interest learning analyzed was used normalized gain (N-Gain) and t-test. The descriptive analysis of interest learning’s post test experiment class shows that N-Gain was 0.35 in medium category and control class was 0.2 in lower category. This proved by inferential analysis, the analyzed shows t(68) = 2.079 p = 0.041 means p < 0.05, then Ho is rejected. Which means that there are difference in interest of learning between experiment class and control class. It can therefore be concluded that the implementation of creative problem solving model can be increase the interest of learning in SMAN 1 Tambusai Utara.Key Words: Creative Problem Solving (CPS), Student Interest Learning, Dynamic Electrical